MANAJEMEN PEMULIHAN PASCABENCANA GEMPA BUMI CIANJUR TAHUN 2022 DALAM PERSPEKTIF KEBIJAKAN PUBLIK - Suhaeti Suhaeti; Syarkawi Syarkawi; Pirma Windra; Muhammad Akbar Maulana; Muhammad Dwi Nurfaisal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to examine how post-disaster recovery management for the 2022 Cianjur Earthquake was implemented, with a primary focus on the rehabilitation and reconstruction phases after the emergency response period ended. The method used is a literature study, namely by examining various written sources such as official government documents, reports from related institutions, laws and regulations-especially Law Number 24 of 2007 concerning Disaster Management-as well as scientific articles and publications relevant to post-disaster recovery issues. The discussion of this research focuses on the recovery process in Cianjur Regency, which includes physical, social, economic, and public service aspects, including how inter-agency coordination is carried out in the implementation of rehabilitation and reconstruction. The results of the study indicate that post-disaster recovery management for the Cianjur Earthquake has basically referred to the national regulatory framework, but in practice still faces various obstacles, such as weak coordination, inaccurate damage data, and slow recovery of the lives of affected communities. Through this research, it is hoped that it can provide both conceptual and practical contributions for local governments and stakeholders in strengthening post-disaster recovery management to be more effective, integrated, and sustainable in accordance with the provisions of laws and regulations. Keyword : Post-Disaster Recovery, Cianjur Earthquake, Rehabilitation and Reconstruction, Disaster Management